Clinical Profile of CNS Non-MS Inflammatory Demyelinating Diseases: A Cross-Sectional Observational Study from a Tertiary Care Hospital at Srinagar - Noor, Murtaza; Asimi, Ravouf; Mir, Feroze A; Wani, Mohammad Maqbool; Masoom, Injeela (National Journal of Medical Research, 2025)
Background: Inflammatory non-MS CNS demyelinating diseases includes a heterogeneous group of diseases with varying clinical presentation, extent of neural axis involvement and phenotype severity. This study was done to describe the demographic profile and clinical phenotype of these groups of diseases in order to provide data on the local patterns of disease presentation. Methods: A cross-sectional observational study comprising 65 patients was performed at Sher-i-Kashmir Institute of Medical Sciences (SKIMS), Srinagar between October 2022 to June 2024 and data was collected on detailed demographic and clinical profile. Appropriate statistical methods were then applied and data analysis was done. Results: Neuromyelitis Optica Spectrum Disorder (NMOSD, 40%), Myelin Oligodendrocyte Glycoprotein Antibody Disease (MOGAD, 21.5%), and Acute Disseminated Encephalomyelitis (ADEM, 13.8%) were most common, followed by idiopathic primary central nervous system (CNS) demyelination, optic neuritis (ON), and longitudinally extensive transverse myelitis (LETM). Mean age was 40.2 years; 41.5% were aged 21–40. Among 15 pediatric cases, MOGAD, ADEM, and idiopathic ON predominated. NMOSD and MOGAD showed recurrent disabling patterns affecting spinal cord and optic nerves, while ADEM and CNS demyelination involved supratentorial regions; idiopathic LETM and ON affected spine and optic nerves exclusively. Conclusion: The study reflects the clinical heterogeneity amongst various groups of non-MS CNS inflammatory demyelinating diseases and also provides data on local demographic patterns.